Analisis Pengaruh Penerapan Good Corporate Governance (GCG) terhadap Kinerja Keuangan pada Perusahaan Manufaktur Sektor Makanan dan Minuman yang Terdaftar di Bursa Efek Indonesia (BEI) Periode 2022-2024 - Septi Novalia; Puji Astuti; Diah Nurdiwaty (Jurnal Penelitian Ekonomi Manajemen dan Bisnis, 2026)
This study aims to analyze and empirically examine the effect of Good Corporate Governance mechanisms, including institutional ownership, managerial ownership, and independent commissioners, on the financial performance of food and beverage sub-sector companies listed on the Indonesia Stock Exchange (IDX) during the 2022-2024 period. This research employs a quantitative approach using multiple linear regression analysis to determine the relationships and the magnitude of influence among the research variables. The data used are secondary data obtained from the companies’ officially published annual financial reports. The results indicate that partially, institutional ownership has a positive and significant effect on financial performance, suggesting the presence of effective external monitoring. In contrast, managerial ownership and independent commissioners have a negative and significant effect on financial performance. Simultaneously, the three variables significantly affect financial performance, with an Adjusted R Square value of 0.326, indicating that the model explains 32.6% of the variation in financial performance. These findings demonstrate that Good Corporate Governance mechanisms play a relatively important role in influencing corporate financial performance, although other factors outside the research model also contribute to the variation.